Trading Gain, Environmental Pains of Bitcoin Activity: Emissions, Electricity, and Electronic Waste - Adam, Joshua; Ricko, Ricko; Wijaya, Singgih Almando; Fitriya, Fitriya (International Journal of Energy Economics and Policy, 2025)
This study was conducted to examine the impact of rising bitcoin activity on carbon emissions, electricity consumption, and e-waste. The study utilizes data from 2020 to 2023 and applies Ordinary Least Squares (OLS) regression analysis, addressing potential issues such as heteroscedasticity, autocorrelation, and multicollinearity. The results of this study show that Bitcoin return and volume have a significant effect on increasing the amount of carbon emissions, while greater volatility may slightly reduce emissions. Global electricity consumption is significantly affected by Bitcoin volatility and hashrate. The amount of global e-waste is strongly influenced by transaction volume and mining activity. These findings remain robust under OLS, Robust Standard Errors, and Newey-West estimations, aligning with previous studies on the environmental impact of cryptocurrency. Suggesting rising Bitcoin activity indicates a measurable environmental impact, arguing needs for stronger regulatory oversight and development of more environmentally friendly technologies. This research distinguishes itself from previous studies by not solely focusing on cryptocurrency mining. Instead, it also analyzes how the increasing volume of cryptocurrency transactions directly contributes to rising carbon emissions, electricity consumption, and electronic waste.